2017
DOI: 10.12681/eh.11548
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of a Beauveria bassiana strain, Bacillus thuringiensis and their combination against the tomato leafminer Tuta absoluta

Abstract: A single leaf bioassay was developed to investigate the entomopathogenic efficacy of a Beauveria bassiana strain, Bacillus thuringiensis (Costar®) and their interactions on larval mortality of Tuta absoluta (Meyrick) (Lepidoptera: Gelechiidae). Tomato leaves were removed from the plants and sprayed with manufacturers' highest field recommended concentrations for tomato crops before or after infesting the leaves with the larvae. Third instar larvae proved the most susceptible, while susceptibility was lower in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
8
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 8 publications
1
8
1
Order By: Relevance
“…Similarly, other isolates of B. bassiana scored LC 50 values of 4.5 × 10 5 and 3.6 × 10 5 spores·ml -1 against second and third instar larvae of T. absoluta , respectively [ 65 ]. Usually, when the spore concentration and exposure time increases concurrently, larval mortality also increases in all evaluated strains of B. bassiana , which is comparable with other findings [ 61 , 63 , 65 ].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Similarly, other isolates of B. bassiana scored LC 50 values of 4.5 × 10 5 and 3.6 × 10 5 spores·ml -1 against second and third instar larvae of T. absoluta , respectively [ 65 ]. Usually, when the spore concentration and exposure time increases concurrently, larval mortality also increases in all evaluated strains of B. bassiana , which is comparable with other findings [ 61 , 63 , 65 ].…”
Section: Discussionsupporting
confidence: 91%
“…Furthermore, these pathogenically valued isolates of B. bassiana showed almost equal efficacy against both second and third instar larvae of T. absoluta by scoring 95.7% and 95% of mortality, respectively, which is contradicting to reports of Tsownara and Port [ 63 ] which showed that third instar larvae of T. absoluta is more susceptible to B. bassiana than the second instar larvae. In addition, these isolates produced considerable (4.6 × 10 6 to 3.5 × 10 7 spores·ml -1 ) amount of spores over the dead larval cadavers.…”
Section: Discussioncontrasting
confidence: 82%
“…Previous works had shown a synergistic effect of different treatments on its fitness. For example, the combination of B. bassiana and B. thuringiensis strongly reduced T. absoluta larvae survival (Tsoulnara and Port, 2016). Yet, the usefulness of co-expression of different proteinase inhibitors to enhance plant resistance to T. absoluta has been highlighted (Hamza et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…In another study conducted under field conditions, a mortality rate of 75.9% was determined with Dipel ® 2X (Btk, 6.4%, 100 g/100 l concentration) (Moussa et al, 2013). As a result of the highest rate of application of Costar ® , one of the commercial preparats, under field conditions, reported that the 3 rd instar larvae showed higher sensitivity than the 2 nd instar larvae (Tsoulnara and Port, 2016). In another study, the commercial preparats were 70% effective for Delfin ® and 59% for Rebound at the licensed concentration (Catalbudak et al, 2018).…”
Section: Discussionmentioning
confidence: 99%